Analysis of the State of Energy Metabolism and Autonomic Nervous System of Children and Adolescents in the Aral Sea Region (Republic Of Karakalpakstan) - Utemuratov A. Najimatdin; Matchanov T. Azat; Khushmatov S. Shunkor (Zien Journals, 2023)
This work explains that, pupils from grades 1 through 11 at school No. 8 in the city of Nukus, the Republic of Karakalpakstan, had their minimum and maximum heart rates measured at 83.73±4.36 beats per minute (bpm) for boys and 79.32±2.26 beats per minute (bpm) for girls. They also had their systolic blood pressure measured at 85.16±4.15 beats per minute (bpm) for boys and 89.37±4.09 beats per minute (bpm) for girls. The Robinson index's minimum/maximum values for boys are 73.43±4.26/104.18±2.37, and 75.38±3.17/102.43±5.27 for girls, respectively. The mechanisms of energy exchange in the body were rated as "excellent" in the overall condition of boys and girls aged 7 to 10, and "poor" in the age range of 11 to 17 years. A minimum/maximum range of 23.18±1.05/42.32±1.24 was seen for the Kerdo index values in investigations including school children in grades 1-11. Contrarily, the autonomic nervous system in schoolchildren was entirely "sympathetic" meaning that the sympathetic nervous system was given primacy. For boys, this was 16.80±0.89 and for girls, it was 38.50±1.05.
Keywords: heart rate; systolic; Robinson index